Studi berbagai jenis sarang permanen untuk mengembangbiakkan semut hitam, Dolichoderus thoracicus (Smith) (Hymenoptera: Formicidae) - Ahmad Saleh (Perhimpunan Entomologi Indonesia, 2012)
Black ants, Dolichoderus thoracicus (Smith) (Hymenoptera: Formicidae) is one of the biological agents that can be used to control the cocoa pod borer Conopomorpha cramerella and Helopeltis sp. To effectively prevent C. cramerella infestation, high population of black ants are required. Population growth of black ants in three types of permanent nests and non permanent nest were observed during 3 months. Every month, five nests of each type were taken at random and then all stadia were calculated. The permanent nests will support ant population for some years and the black ant population per nest is higher when compared to nest made of dried cocoa leaves only. Permanent nests are made of 75 pieces of dried cocoa leaves which are placed in plastic bags with ventilation holes. In the longer term permanent black ant nests are more cost effective then ant nests which have been made from only dried leaves because frequent replacement is not required. Permanent ant nests will also ensure a stable black ant population is maintained.